Frequency of third trimester umbilical artery Doppler for improving neonatal outcomes in high-risk pregnancies: a randomized trial - Mohamed Hamed Salama; Hanan Hanna Rizk; Maii Nawara (Korean Society of Obstetrics and Gynecology, 2023)
Objective Umbilical artery Doppler ultrasonography is useful for high-risk prenatal surveillance. However, according to a systematic review and meta-analysis by the Cochrane pregnancy and childbirth group, the optimal frequency with which such surveillance should occur remains unclear. In the current study, we aimed to investigate whether performing umbilical artery Doppler on a weekly basis enables earlier detection of changes in utero-placental blood flow than the recommended bi-weekly (i.e., fortnightly) regimen and its impact on perinatal outcomes. Methods This randomized controlled study included 292 high-risk pregnant women in their third trimester who attended the Ain Shams University Maternity Hospital in Egypt from January 2018 to September 2019. The women were randomly assigned to two groups to undergo either bi-weekly or once-weekly umbilical artery Doppler ultrasound. Results In the primary analysis performed according to the intention-to-treat basis, we observed no difference in the primary outcome of fetal admission to the neonatal intensive care unit (NICU) within the first 24 hours (risk difference, −2.63; 95% confidence interval, −12.92 to 7.65). Furthermore, no significant differences in secondary outcomes were observed (apart from stillbirth). Conclusion Weekly umbilical artery Doppler is not superior to bi-weekly surveillance in preventing admission to the NICU and most other studied outcomes. Therefore, the bi-weekly regiment may be more convenient for women and more cost-effective for health care organizations (trial registration: NCT03584763 at clinicaltrials.gov).